Efficacy and Safety of Pergoveris in Assisted Reproductive Technology—ESPART: rationale and design of a randomised controlled trial in poor ovarian responders undergoing IVF/ICSI treatment. Issue 7 (3rd July 2015) - Humaidan, P; Schertz, J; Fischer, R
Abstract : Introduction: The results of a recent meta-analysis showed that adding recombinant human luteinising hormone (r-hLH) to recombinant human follicle-stimulating hormone (r-hFSH) for ovarian stimulation was beneficial in poor responders, resulting in a 30% relative increase in the clinical pregnancy rate compared with r-hFSH monotherapy. However, a limitation of the meta-analysis was that the included studies used heterogeneous definitions of poor ovarian response (POR). Furthermore, the use of r-hLH supplementation during ovarian stimulation is a topic of ongoing debate, and well-designed, adequately powered, multicentre, randomised controlled trials in this setting are warranted. Therefore, the objective of the ESPART trial is to explore the possible superiority of a fixed-dose combination of r-hFSH plus r-hLH over r-hFSH monotherapy in patients with POR, as per a definition aligned with the European Society of Human Reproduction and Embryology (ESHRE) Bologna criteria. Methods and analysis: Phase III, randomised, single-blind, parallel-group trial in women undergoing in vitro fertilisation and/or intracytoplasmic sperm injection. Approximately 946 women aged 18–<41 years from 18 countries will be randomised (1:1) to receive a fixed-dose combination of r-hFSH plus r-hLH in a 2:1 ratio (Pergoveris) or r-hFSH monotherapy (GONAL-f). The primary end point is the total number of retrieved oocytes per participant. Secondary end points include: ongoing pregnancy rate, live birth rate, implantation rate, biochemical pregnancy rate and clinical pregnancy rate. Safety end points include: incidence and severity of ovarian hyperstimulation syndrome, and of adverse events and serious adverse events. Ethics and dissemination: The study will be performed in accordance with ethical principles that have their origin in the Declaration of Helsinki, with the International Conference on Harmonisation–Good Clinical Practice guidelines and all applicable regulatory requirements. All participants will provide written informed consent prior to entry. The results of this study will be publically disseminated. Trial registration numbers: ClinicalTrials.gov identifier: NCT02047227 ; EudraCT Number: 2013-003817-16; Clinical Trial Protocol Number: EMR200061-005 V.3.0, 15 April 2014.